2010
DOI: 10.1161/hypertensionaha.110.158220
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II–Mediated Microvascular Thrombosis

Abstract: Abstract-Hypertension is associated with an increased risk of thrombosis that appears to involve an interaction between the renin-angiotensin system and hemostasis. In this study we determined whether angiotensin II-mediated thrombosis occurs in arterioles and/or venules and assessed the involvement of type 1 (AT 1 ), type 2 (AT 2 ), and type 4 (AT 4 ) angiotensin II receptors, as well as receptors for endothelin 1 and bradykinin 1 and 2 in angiotensin II-enhanced microvascular thrombosis. Thrombus development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 41 publications
4
112
0
9
Order By: Relevance
“…Reviewed in Garg et al (2012). Actions in the clotting system Platelet aggregation Platelet Increases platelet aggregation by a mechanism that involves AT1 receptor, AT2 receptor, and AT4 receptor (Senchenkova et al, 2010). Stimulates platelet activating factor synthesis (Neuwirth et al, 1989).…”
Section: Small and Large Intestinementioning
confidence: 99%
“…Reviewed in Garg et al (2012). Actions in the clotting system Platelet aggregation Platelet Increases platelet aggregation by a mechanism that involves AT1 receptor, AT2 receptor, and AT4 receptor (Senchenkova et al, 2010). Stimulates platelet activating factor synthesis (Neuwirth et al, 1989).…”
Section: Small and Large Intestinementioning
confidence: 99%
“…The concentration for half-maximum velocity (EC 50 ) for aggregation velocity of WT platelets in response to either thrombin or ADP was determined as described previously. 29 This method yielded an EC 50 of 0.63 U/mL for thrombin and 733nM for ADP. The EC 50 values were used to determine whether platelet aggregation velocity differed between control (WT3WT) and ␤ s 3WT mice.…”
Section: Platelet Aggregationmentioning
confidence: 97%
“…ANS was administered (75 g/mouse) IP 24 hours before the experiment. 29,30 A reduction in circulating neutrophils (1% Ϯ 5% in WT3WT and 88% Ϯ 6% in ␤ s 3WT) was verified by counting neutrophils in the peripheral blood before ANS injection and immediately before the experiment. ANS did not alter the number of circulating lymphocytes, monocytes, or platelets.…”
mentioning
confidence: 99%
“…In vitro studies confirmed that Ang II induces the expression of TF in rat aortic endothelial cells [76] and human monocytes [77]. Chronic Ang II infusion induces platelet-endothelial cell adhesion [78] and accelerates thrombus formation in both large arteries [71,79] and arterioles [74]. TF in atherosclerotic plaques initiates blood coagulation, directly stimulates SMC proliferation and activates MMPs capable of degrading collagen.…”
Section: Role Of Ras In Atherosclerosis Progression and Acute Complicmentioning
confidence: 76%
“…The role of Ang II, as a mediator of thrombogenesis has been also supported by animal studies [71,72]. Namely, models of elevated Ang II levels, elicited both genetically and via chronic Ang II infusion, have demonstrated increased tissue factor (TF) expression and increased plasma plasminogen activator inhibitor-1 (PAI-1) level [73][74][75]. In vitro studies confirmed that Ang II induces the expression of TF in rat aortic endothelial cells [76] and human monocytes [77].…”
Section: Role Of Ras In Atherosclerosis Progression and Acute Complicmentioning
confidence: 99%